Unpacking the concept of political will to confront corruption - Brinkerhoff, Derek W. (U4 Anti-Corruption Resource Centre, 2010)
Quite often, "lack of political will" is identified as the culprit for poorly performing anti-corruption programmes. Yet despite the frequen cy with which it is used to explain unsatisfactory reform outcomes, po litical will remains under-defined and poorly understood. Further, ass essments are often conducted retrospectively, looking back at failed p rogrammes. By applying a model of political will that specifies a set of action-based components that are observable and measurable, and ame nable to external reinforcement and support, more clarity regarding th e degree of political will can be achieved.